EFFECT OF COMBINED ENDURANCE AND BREATHING EXERCISES ON IMMUNE FUNCTION AND RESPIRATORY PERFORMANCE IN PULMONARY TUBERCULOSIS: A QUASI EXPERIMENTAL STUDY (Proceedings OPTIMAL, 2026)
Pulmonary tuberculosis remains a major public health problem in Indonesia, often accompanied by prolonged recovery due to impaired immune function and reduced respiratory muscle performance. In addition to pharmacological treatment, complementary non-pharmacological interventions are required to support optimal recovery. This study aimed to analyze the effect of a combination of endurance exercise and breathing exercise on immune system parameters and respiratory muscle performance in patients with pulmonary tuberculosis undergoing Anti-Tuberculosis Drug (OAT) therapy. A quasi-experimental study with a pre-test and post-test design without a control group was conducted involving 20 pulmonary tuberculosis patients recruited purposively from a primary health care center in Cilacap, Indonesia. The intervention was implemented for four weeks, three times per week, consisting of moderate-intensity endurance exercise and structured breathing exercises. Immune function was evaluated using total leukocyte count and lymphocyte percentage, while respiratory muscle performance was assessed using peak expiratory flow rate (PEFR). Data were analyzed using paired sample t-tests and Pearson correlation tests. The results showed a significant increase in leukocyte count, lymphocyte percentage, and PEFR after the intervention (p < 0.05). A positive correlation was also identified between improvements in immune parameters and respiratory muscle performance. These findings suggest that the combination of endurance and breathing exercises is effective in enhancing immune response and respiratory function in pulmonary tuberculosis patients and may be developed as a feasible community-based physiotherapy intervention in primary care settings